Tailoring the Electrochemical Behaviors of Bismuth Ferrite Using Ca Ion Doping - Ma, Chao-Jie; Li, Na; Song, Wei-Li (Frontiers in Materials, 2020)
Bismuth ferrite (BFO) is considered as a significant (ABO3) perovskite ceramic in electronics and energy storage. Since the A site (Bi3+) presents electrochemical active feature, electrochemical performance of perovskite bismuth ferrite for serve as an electrode material is improved by proper calcium ions doping in the aqueous basic electrolyte environment. For substantially promoting the electronic transport capabilities, Ca2+ ions are used for substituting partial Bi3+ ions at A site introducing oxygen vacancies. The electrochemical performance suggests that utilization of 10% Ca2+ doping (BFO-10%Ca) would offer 305.5 mAh g-1 at 1 A g-1. Specifically, the assembled BFO-10%Ca //graphene asymmetric energy storage devices could deliver a stable energy storage capability up to 3000 cycles at a current density of 5 A g-1. The results indicate that heterogeneous ion doping would be effective strategy for improving the electrochemical performance for application energy storage.